Penerapan Restorative Justice Dalam Penyelesaian Tindak Pidana Penggelapan Di Kejaksaan Negeri Klaten - Dessy Permata Diani; Sulistyanta Sulistyanta (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
This research was conducted with the aim of finding out the application and obstacles to restorative justice in resolving the crime of embezzlement at the Klaten District Prosecutor's Office. This research uses a type of juridical-empirical research, namely research by collecting data through interviews. This research uses material collection techniques through interviews and observations as well as literature study. The crime of embezzlement is one of the crimes that can be implemented by restorative justice efforts, because in general this crime is a property crime that can be restored to the goods or objects that are the object of the crime of embezzlement so that when the restoration to its original condition is fulfilled, then the criminal case is there is no need to continue the legal process. The results of this research indicate that the application of restorative justice in resolving the crime of embezzlement at the Klaten District Prosecutor's Office is guided by the Republic of Indonesia Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The implementation of the restorative justice process does not always run smoothly, there are several obstacles. However, this obstacle is not a serious problem so it can be overcome by the Klaten District Prosecutor's Office.